2020
DOI: 10.1097/rlu.0000000000003376
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Sarcoma With Low 18F-FDG Uptake

Abstract: A 75-year-old man presented with dyspnea for more than 2 months, with blood test showing low platelet count and cardiac ultrasound showing severe pulmonary hypertension (>54 mm Hg). A CT pulmonary angiogram showed a filling defect in the pulmonary trunk, right and left pulmonary arteries, raising the possibilities of pulmonary embolism or artery sarcoma. FDG PET/CT was performed for further evaluation and showed low uptake in the pulmonary wall, which supported the diagnosis of pulmonary embolism. Patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…2 Although pulmonary artery sarcoma usually shows higher FDG uptake than thromboembolism, 3,4 it may show low FDG uptake probably due to low cellularity and the presence of myxoid matrix and necrosis, mimicking thromboembolism. [7][8][9][10] Several case reports and articles have shown the usefulness of FAPI PET in the detection and staging of sarcoma. 6,[11][12][13][14][15] A prospective study showed 68 Ga-FAPI PET was a valuable diagnostic tool in patients with sarcoma and had a high positive predictive value and sensitivity for sarcoma staging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although pulmonary artery sarcoma usually shows higher FDG uptake than thromboembolism, 3,4 it may show low FDG uptake probably due to low cellularity and the presence of myxoid matrix and necrosis, mimicking thromboembolism. [7][8][9][10] Several case reports and articles have shown the usefulness of FAPI PET in the detection and staging of sarcoma. 6,[11][12][13][14][15] A prospective study showed 68 Ga-FAPI PET was a valuable diagnostic tool in patients with sarcoma and had a high positive predictive value and sensitivity for sarcoma staging.…”
mentioning
confidence: 99%
“…Intimal sarcoma of the pulmonary artery is a rare malignant tumor mimicking pulmonary thromboembolism clinically and radiologically 2. Although pulmonary artery sarcoma usually shows higher FDG uptake than thromboembolism,3,4 it may show low FDG uptake probably due to low cellularity and the presence of myxoid matrix and necrosis, mimicking thromboembolism [7][8][9][10]. Several case reports and articles have shown the usefulness of FAPI PET in the detection and staging of sarcoma 6,[11][12][13][14][15].…”
mentioning
confidence: 99%
“…On 18 F-FDG PET/CT, AFH was commonly hypermetabolic 5,7. The differential diagnosis of pulmonary artery AFH includes septic PE, pulmonary artery fibrous tumor, sarcoma, and so on 2,3,5. Microscopically, a thick fibrous pseudocapsule, infrequent mitoses, blood-filled endothelial-lined cystic cavities, and a rim of dense lymphoplasmacytic infiltrate suggest the diagnosis 8,9.…”
mentioning
confidence: 99%
“…5,7 The differential diagnosis of pulmonary artery AFH includes septic PE, pulmonary artery fibrous tumor, sarcoma, and so on. 2,3,5 Microscopically, a thick fibrous pseudocapsule, infrequent mitoses, blood-filled endothelial-lined cystic cavities, and a rim of dense lymphoplasmacytic infiltrate suggest the diagnosis. 8,9 Fluorescence in situ hybridization analysis revealed rearrangement of EWSR, which was confirmed by RT-PCR as EWSR1-ATF1 fusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation